Elusive Interdisciplinarity in International Law in the Nordics - Korhonen, Outi (Brill Nijhoff, 2025)
In this article we discuss the interdisciplinarity as a practical question and a theoretical challenge. We place international law on a disciplinary map and advocate for theoretical openings towards other social sciences using the critique on methodological nationalism in social sciences as an example of possibilities for broadening the theoretical approaches. We suggest that methodological dialogue should be taken as central in research practices. We also inquire into interdisciplinarity practices that include theoretical openness towards other disciplines and explain how they could benefit legal scholars particularly when analysing consequences of the law. A number of examples from the interdisciplinarity in Nordic countries are included and some of their approaches and terminological challenges discussed.